Nurses' work at Family Health Strategy: possibilities to operate health needs - Anna Maria Meyer Maciel Rodríguez; Silvana Martins Mishima; Angelina Lettiere-Viana; Silvia Matumoto; Cinira Magali Fortuna; Débora de Souza Santos (Associação Brasileira de Enfermagem, 2020)
ABSTRACT Objectives: to identify and analyze possibilities for recognizing health needs in the nurses' work at Family Health Strategy. Methods: a qualitative study with interviews and observation of the nurses' work in the countryside of São Paulo. The empirical material was subjected to thematic content analysis and interpreted in the light of the health work process. Results: two themes emerged: Possibilities utilized and Possibilities neglected to recognize health needs. Careful observation, welcoming, attention, listening, bonding and dialogue developed by nurses, in live work in action with users, touched on the possibilities, which, taken advantage of, were evidenced in care in spontaneous demand, scheduled consultation, examination gynecological and group activities. Final Considerations: nurses are able to recognize health needs, which can expand their clinical practice and interprofessionality in Family Health.